Multistate voter model with imperfect copying - Vazquez, Federico (2019)
The voter model with multiple states has found applications in areas as diverse as population genetics, opinion formation, species competition, and language dynamics, among others. In a single step of the dynamics, an individual chosen at random copies the state of a random neighbor in the population. In this basic formulation, it is assumed that the copying is perfect, and thus an exact copy of an individual is generated at each time step. Here, we introduce and study a variant of the multistate voter model in mean field that incorporates a degree of imperfection or error in the copying process, which leaves the states of the two interacting individuals similar but not exactly equal. This dynamics can also be interpreted as a perfect copying with the addition of noise: a minimalistic model for flocking. We found that the ordering properties of this multistate noisy voter model, measured by a parameter ψ in [0,1], depend on the amplitude η of the copying error or noise and the population size N . In the case of perfect copying η = 0 , the system reaches an absorbing configuration with complete order ( ψ = 1 ) for all values of N . However, for any degree of imperfection η > 0 , we show that the average value of ψ at the stationary state decreases with N as ⟨ ψ ⟩ ≃ 6 / ( π 2 η 2 N ) for η ≪ 1 and η 2 N ≳ 1 , and thus the system becomes totally disordered in the thermodynamic limit N → ∞ . We also show that ⟨ ψ ⟩ ≃ 1 − π 2 6 η 2 N in the vanishing small error limit η → 0 , which implies that complete order is never achieved for η > 0 . These results are supported by Monte Carlo simulations of the model, which allow to study other scenarios as well.